Three different episodes of prompt equatorial electric field perturbations under steady southward IMF Bz during St. Patrick's day storm - Tulasiram, S.; Veenadhari, B. (My University, 2019)
Three different episodes of prompt penetration electric field (PPEF) disturbances are observed during the main phase of the St. Patrick's Day storm on 17 March 2015 under steady southward interplanetary magnetic field (IMF) Bz conditions unlike the conventional PPEF associated with southward or northward turnings of IMF Bz. These PPEF events took place during the period when strong disturbance dynamo fields are prevailing in the background. The first event is triggered by a solar wind dynamic pressure pulse that caused a sharp eastward PPEF and strong enhancement of equatorial electrojet current in Brazilian dayside. The second event caused another short but strong westward PPEF on dayside due to the reversal of IMF By from duskward to dawnward under steady IMF Bz. The third event caused a longer eastward PPEF in association with a solar wind dynamic pressure pulse followed by the onset of a substorm, which has led to strong enhancement of equatorial electrojet, quick rejuvenation and symmetric redistribution of equatorial ionization anomaly in the Brazilian sector. The signatures of the PPEF with opposite polarity and smaller magnitudes are also observed in the Asian sector on the nightside. The possible mechanisms for the observed PPEF events under steady IMF Bz are discussed in terms of changes in the high‐latitude field‐aligned currents and reconfiguration of high‐latitude convection fields using Active Magnetosphere and Planetary Electrodynamics Response Experiment and Super Dual Auroral Radar Network high‐frequency radar observations.
Keywords: EQUATORIAL AERONOMY, Patrick's day storm, Equatorial Electric Field Perturbations